Functional dissociation of the language network and other cognition in early childhood - Hiersche, K. J.; Schettini, E.; Li, J.; Saygin, Z. M. (Human brain mapping, 2024)
Is language distinct from other cognition during development? Does neural machinery for language emerge from general‐purpose neural mechanisms, becoming tuned for language after years of experience and maturation? Answering these questions will shed light on the origins of domain‐specificity in the brain. We address these questions using precision fMRI, scanning young children (35 months to 9 years of age) on an auditory language localizer, spatial working memory localizer (engaging the domain‐general multiple demand [MD] network), and a resting‐state scan. We create subject‐specific functional regions of interest for each network and examine their selectivity, specificity, and functional connectivity. We find young children show domain‐specific, left‐lateralized language activation, and that the language network is not responsive to domain‐general cognitive load. Additionally, the cortically adjacent MD network is selective to cognitive load, but not to language. These networks show higher within versus between‐network functional connectivity. This connectivity is stable across ages (examined cross‐sectionally and longitudinally), whereas language responses increase with age and across time within subject, reflecting a domain‐specific developmental change. Overall, we provide evidence for a double dissociation of the language and MD network throughout development, in both their function and connectivity. These findings suggest that domain‐specificity, even for uniquely human cognition like language, develops early and distinctly from mechanisms that presumably support other human cognition. Using both cross‐sectional and longitudinal data, we show that the language network is domain‐specific and distinct from the multiple demand network in its functional activation and functional connectivity.